2018
DOI: 10.1111/adb.12587
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture inhibition of methamphetamine‐induced behaviors, dopamine release and hyperthermia in the nucleus accumbens: mediation of group II mGluR

Abstract: Methamphetamine (METH) increases metabolic neuronal activity in the mesolimbic dopamine (DA) system and mediates the reinforcing effect. To explore the underlying mechanism of acupuncture intervention in reducing METH-induced behaviors, we investigated the effect of acupuncture on locomotor activity, ultrasonic vocalizations, extracellular DA release in the nucleus accumbens (NAcs) using fast-scan cyclic voltammetry and alterations of brain temperature (an indicator of local brain metabolic activity) produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Ultrasonic vocalizations (USVs) emitted by rats in response to acupuncture stimulation were recorded using customized sound-attenuating chambers as previously described [17]. The chamber consisted of two boxes to minimize exterior noise (inside box: 60 × 42 × 42 cm, outside box: 68 × 50 × 51 cm).…”
Section: Recordings Of Ultrasonic Vocalizations (Usvs)mentioning
confidence: 99%
“…Ultrasonic vocalizations (USVs) emitted by rats in response to acupuncture stimulation were recorded using customized sound-attenuating chambers as previously described [17]. The chamber consisted of two boxes to minimize exterior noise (inside box: 60 × 42 × 42 cm, outside box: 68 × 50 × 51 cm).…”
Section: Recordings Of Ultrasonic Vocalizations (Usvs)mentioning
confidence: 99%
“…The effectiveness and safety of acupuncture for TS has been confirmed by numerous clinical studies (Wu et al, 1996; Ma et al, 2006; Zhu et al, 2009; Tang et al, 2015; Yu et al, 2016; Lee, 2017), but the underlying mechanisms remain unclear. Previous studies have demonstrated that acupuncture can regulate the DA system (Bo et al, 2017; Lin et al, 2017; Kim et al, 2018; Xiao et al, 2018). DA plays an important role in the recovering effect of acupuncture on motor functions (Cabyoglu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(Kim G. H. et al, 2010) reported that manual twisting is more effective than the lifting-thrusting technique in producing analgesic effects on formalin-induced pain in rats. We and others have shown that manual twisting of needles applied to HT7 acupoints suppresses addictive behaviors induced by abused drugs, including cocaine, methamphetamine, and ethanol (Yang et al, 2010; Jin et al, 2018; Kim et al, 2018). Moreover, acupuncture at HT7 attenuates drug-induced dopamine release and metabolic neuronal activity in the nucleus accumbens (Yoon et al, 2004; Jin et al, 2018) through group II metabotropic glutamate receptors (Kim et al, 2018) and modulation of GABA neuron activity in the ventral tegmental area (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that manual twisting of needles applied to HT7 acupoints suppresses addictive behaviors induced by abused drugs, including cocaine, methamphetamine, and ethanol (Yang et al, 2010; Jin et al, 2018; Kim et al, 2018). Moreover, acupuncture at HT7 attenuates drug-induced dopamine release and metabolic neuronal activity in the nucleus accumbens (Yoon et al, 2004; Jin et al, 2018) through group II metabotropic glutamate receptors (Kim et al, 2018) and modulation of GABA neuron activity in the ventral tegmental area (Yang et al, 2010). While these studies provide evidence that twisting acupuncture needle manipulation produces therapeutic effects, manual acupuncture stimulation could alter its effect by affecting many vagaries, including rotation durations and angles.…”
Section: Discussionmentioning
confidence: 99%